Regenerated positive electrode active material, regenerating method thereof, and secondary battery including the same

The heat-treatment and regeneration method for cathode active materials from waste lithium batteries addresses environmental and cost issues by recovering the crystal structure and surface coating, enhancing battery performance and efficiency without using acids or solvents.

JP2025500137AActive Publication Date: 2025-01-09LG ENERGY SOLUTION LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024531456
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-05-09
Filing Date
2023-10-11
Publication Date
2025-01-09
Estimated Expiration
2043-10-11

AI Technical Summary

Technical Problem

Existing methods for recycling cathode active materials from waste lithium secondary batteries are environmentally harmful, costly, and result in reduced battery performance due to the use of acids, neutralization processes, and generation of toxic gases, with issues such as foreign matter on the surface of recycled materials and changes in particle size distribution.

Method used

A method involving heat-treatment of waste cathodes to decompose binders and conductive materials, followed by separation of the current collector, addition of a lithium precursor and Co-containing coating agent, and annealing to recover the crystal structure and surface coating layer, without using acids or organic solvents, thereby regenerating the positive electrode active material.

Benefits of technology

This process results in a recycled positive electrode active material with improved initial capacity and resistance characteristics, reduced production costs, and enhanced economic efficiency, while being environmentally friendly by eliminating the need for neutralization and wastewater treatment, and avoiding toxic gas generation or explosions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500137000001_ABST
    Figure 2025500137000001_ABST
Patent Text Reader

Abstract

The present invention relates to a recycled positive electrode active material, a regenerating method thereof, and a secondary battery including the same. More specifically, the present invention relates to a recycled positive electrode active material, a regenerating method thereof, and a secondary battery including the same, which are characterized by comprising the steps of: (a) heat-treating a waste positive electrode having a positive electrode active material layer formed on a current collector, thereby thermally decomposing a binder and a conductive material in the positive electrode active material layer, thereby separating the current collector from the positive electrode active material layer and recovering the positive electrode active material in the positive electrode active material layer; and (b) adding a lithium precursor and a Co-containing coating agent to the recovered positive electrode active material, and annealing the resulting material. According to the present invention, a lithium precursor and a Co-containing coating agent are added to a cathode active material obtained by heat-treating a waste cathode, and the cathode active material is annealed. This allows the recovery of the crystal structure and the recovery of the surface coating layer, as well as the advantages of the process, resulting in excellent initial capacity and resistance characteristics of a secondary battery. In addition, since no acid is used in the recovery and regeneration process, it is environmentally friendly and does not require neutralization or wastewater treatment, thereby reducing process costs. Since the cathode active material is regenerated as it is without being decomposed, there are no metal elements to be discarded. Since no organic solvent is used, there is no risk of toxic gas generation or explosion. In particular, since the water washing process is omitted, there is an effect of providing a method for regenerating a cathode active material with greatly improved economy and productivity.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0153126 filed on November 15, 2022 and Korean Patent Application No. 10-2023-0059549 refiled on May 9, 2023 based thereon, and all contents disclosed in the documents of the Korean patent application are incorporated as part of this specification.

[0002] The present invention relates to a regenerated positive electrode active material, a regenerating method thereof, and a secondary battery including the same. More specifically, the present invention relates to a method for regenerating a positive electrode active material, which comprises heat-treating a waste positive electrode including a current collector and a positive electrode active material layer coated thereon to recover the positive electrode active material, and then simultaneously adding a lithium precursor and a Co-containing coating agent and annealing the resulting material, thereby recovering the crystal structure and the surface coating layer, as well as providing process advantages. This method is environmentally friendly because no acid is used in the recovery and regeneration processes, and thus reduces process costs because no neutralization or wastewater treatment is required. The present invention relates to a method for regenerating a positive electrode active material, which is not decomposed but directly regenerated, so that no metal elements are discarded, and no organic solvent is used, so that there is no risk of toxic gas generation or explosion, and in particular, the water washing process is omitted, resulting in significant improvement in economy and productivity. [Background technology]

[0003] A lithium secondary battery mainly comprises a positive electrode in which a positive electrode active material layer is coated on a metal foil such as aluminum, a negative electrode in which a negative electrode active material layer is coated on a metal foil such as copper, a separator that prevents the positive electrode and the negative electrode from mixing, and an electrolyte that allows lithium ions to move between the positive electrode and the negative electrode.

[0004] The positive electrode active material layer mainly uses a lithium-based oxide as the active material, and the negative electrode active material layer mainly uses a carbon material as the active material. However, since the lithium-based oxide generally contains rare metals such as cobalt, nickel, or manganese, much research has been conducted into recovering and reusing rare metals from the positive electrodes of lithium secondary batteries that are discarded after use or from positive electrode scraps generated during the manufacturing process of lithium secondary batteries (hereinafter referred to as "scrap positive electrodes").

[0005] Conventional technology for recovering rare metals from used positive electrodes mostly involves dissolving the used positive electrodes with hydrochloric acid, sulfuric acid, or nitric acid, then extracting cobalt, manganese, nickel, etc. with an organic solvent and using them again as raw materials for synthesizing positive electrode active materials.

[0006] However, the method of extracting rare metals using acid has the disadvantages of causing environmental pollution, requiring a neutralization process and a wastewater treatment process, which significantly increases the process cost, and making it impossible to recover lithium, the main metal in the positive electrode active material.

[0007] In order to overcome these drawbacks, recent studies have been conducted on direct recycled methods that directly recycle the cathode active material from waste cathodes without decomposing it. There are roughly four types of such methods, namely calcination, solvent dissolution, aluminum foil dissolution, and crushing & screening.

[0008] Although the calcination method is a simple process, it has the disadvantages of generating foreign matter on the surface of the regenerated positive electrode active material that reduces the output performance of the battery, generating waste gas, and consuming a large amount of energy.

[0009] In addition, the solvent dissolution method can obtain a regenerated positive electrode active material with a relatively clean surface, but has the disadvantages of poor stability and the need for an expensive solvent recovery process since the solvent used to dissolve the binder, such as N-methyl-2-pyrrolidone (NMP), is a toxic gas and has a risk of explosion.

[0010] In addition, the aluminum foil dissolving method has good process stability, low process costs, and easy binder removal, but has the disadvantages of generating foreign matter that is difficult to remove on the surface of the recycled positive electrode active material, and generating hydrogen gas during the aluminum foil removal process, which may cause an explosion.

[0011] Finally, the crushing and screening method has the advantage of being the simplest process, but has the disadvantages that it is difficult to completely separate the current collector from the positive electrode active material, the particle size distribution of the positive electrode active material changes during the crushing process, and the binder remains, causing the battery characteristics of the recycled positive electrode active material to deteriorate.

[0012] Therefore, there is an urgent need to develop a method for regenerating a positive electrode active material with improved output performance, in an environmentally friendly and safe manner, with fewer steps and at fewer costs, without the metal elements discarded from used positive electrodes. Summary of the Invention [Problem to be solved by the invention]

[0013] In order to solve the above problems of the prior art, the present invention provides a method for regenerating a positive electrode active material, which comprises heat-treating a waste positive electrode including a current collector and a positive electrode active material layer coated thereon to recover the positive electrode active material, and then simultaneously adding a lithium precursor and a Co-containing coating agent and annealing the resulting material. This method has advantages in terms of process, and also provides excellent initial capacity and resistance characteristics of a secondary battery, and is environmentally friendly because no acid is used in the recovery and regeneration process of the positive electrode active material, and does not require neutralization or wastewater treatment, thereby reducing process costs, and regenerating the positive electrode active material without decomposing it, so there are no metal elements to be discarded, and no organic solvent is used, so there is no risk of toxic gas generation or explosion, and in particular, the water washing process is omitted, thereby greatly improving economy and productivity.

[0014] Another object of the present invention is to provide a secondary battery excellent in initial capacity and resistance characteristics.

[0015] The above and other objects of the present invention can be achieved by the present invention described below. [Means for solving the problem]

[0016] In order to achieve the above object, I) the present invention provides a method for regenerating a positive electrode active material, comprising the steps of: (a) heat-treating a waste positive electrode having a positive electrode active material layer formed on a current collector, thereby thermally decomposing a binder and a conductive material in the positive electrode active material layer, thereby separating the current collector from the positive electrode active material layer and recovering the positive electrode active material in the positive electrode active material layer; and (b) adding a lithium precursor and a coating agent to the recovered positive electrode active material, and annealing the resultant.

[0017] II) In I), the positive electrode active material layer may include at least one selected from the group consisting of a nickel-cobalt-manganese (NCM)-based positive electrode active material, a nickel-cobalt-aluminum (NCA)-based positive electrode active material, and a nickel-cobalt-manganese-aluminum (NCMA)-based positive electrode active material, and may include at least 60 mol % of Ni based on 100 mol % of the total of the remaining metals excluding Li.

[0018] III) In the above I) or II), in the step (a), the heat treatment may be carried out at 300 to 650° C. in an oxygen atmosphere.

[0019] IV) In the above I) to III), the oxygen has a purity of 59% or more (O 2 ) may also be used.

[0020] V) In the above I) to IV), the positive electrode active material recovered in the step (a) may include single particles.

[0021] VI) In the above I) to V), in the step (b), the lithium precursor may be added in an amount corresponding to 1 mol % to 40 mol % when the total amount of lithium contained in the recovered positive electrode active material is 100 mol %.

[0022] VII) In the above I) to VI), in the step (b), the coating agent may be a Co-containing coating agent.

[0023] VIII) In I) to VII), in step (b), the coating agent may be added in an amount corresponding to 1 to 25,000 ppm based on the total amount of the recovered positive electrode active material and the additionally added lithium precursor.

[0024] IX) In the above I) to VIII), the lithium precursor is LiOH, Li 2 CO 3 , LiNO 3 , and Li 2It may contain one or more of the following:

[0025] X) In the above I) to IX), the coating agent is a Co-containing coating agent, Co(OH) 2 , Co 2 O 3 , Co 3 (PO 4 ) 2 , CoF 3 , CoOOH, Co(OCOCH 3 ) 2 4H 2 O, Co(NO 3 )·6H 2 O, Co 3 O 4 , Co(SO 4 ) 2 7H 2 O, and CoC 2 O 4 It may be one or more selected from the group consisting of:

[0026] XI) In the above I) to X), the annealing can be carried out at 400 to 800°C.

[0027] In addition, the present invention provides a positive electrode active material which is at least one selected from the group consisting of nickel-cobalt-manganese (NCM)-based positive electrode active materials, nickel-cobalt-aluminum (NCA)-based positive electrode active materials, and nickel-cobalt-manganese-aluminum (NCMA)-based positive electrode active materials, the positive electrode active material containing at least 60 mol % of Ni based on 100 mol % of the total of the remaining metals excluding Li, and containing a coating agent.

[0028] XIII) In the above-mentioned XII), the coating agent may be a Co-containing coating agent.

[0029] XIV) In the above XII) or XIII), the coating agent is a Co-containing coating agent, Co(OH) 2 , Co 2 O 3 , Co 3 (PO4 ) 2 , CoF 3 , CoOOH, Co(OCOCH 3 ) 2 4H 2 O, Co(NO 3 )·6H 2 O, Co 3 O 4 , Co(SO 4 ) 2 7H 2 O, and CoC 2 O 4 It may be one or more selected from the group consisting of:

[0030] XV) In the above XII) to XIV), the positive electrode active material may include single particles.

[0031] XVI) In any of XII) to XV), the positive electrode active material may be a regenerated positive electrode active material.

[0032] The present invention also provides XVII) a secondary battery including the positive electrode active material according to any one of the above XII) to XVI). Effect of the Invention

[0033] According to the present invention, a waste positive electrode including a current collector and a positive active material layer coated thereon is heat-treated to recover the positive active material, and then a lithium precursor and a Co-containing coating agent are simultaneously added and annealed. This provides advantages in terms of process, and also provides recovery of the crystal structure and recovery of the surface coating layer, resulting in excellent initial capacity and resistance characteristics of a secondary battery. In addition, since no acid is used in the recovery and regeneration process of the positive active material, it is environmentally friendly and does not require neutralization or wastewater treatment, thereby reducing process costs. Since the positive active material is regenerated as it is without being decomposed, there are no metal elements to be discarded. Since no organic solvent is used, there is no risk of toxic gas generation or explosion. In particular, since the water washing process is omitted, there is an effect of providing a method for regenerating a positive active material with greatly improved economy and productivity. [Brief description of the drawings]

[0034] The following drawings attached to this specification are illustrative of embodiments of the present invention and, together with the detailed description below, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited to the matters described in these drawings. [Figure 1] 1 is a SEM photograph of a fresh positive electrode active material of Comparative Example 1. [Diagram 2] This is an SEM photograph of the positive electrode active material from which the binder and conductive material have been removed by heat-treating waste positive electrodes. [Diagram 3] 1 is a SEM photograph of a positive electrode active material obtained by heat-treating the waste positive electrodes according to Examples 1 to 4 to remove the binder and conductive material, to which a lithium precursor and a Co-containing coating agent are added, followed by annealing. [Figure 4] 13 is a SEM photograph of a positive electrode active material obtained by heat-treating a waste positive electrode according to Comparative Example 2 to remove a binder and a conductive material, to which only a lithium precursor is added, followed by annealing. [Diagram 5] 1 is a SEM photograph of the positive electrode active material regenerated in Example 4. [Figure 6] 1 is a SEM photograph of the positive electrode active material regenerated in Example 5. [Figure 7] 1 is a graph showing the results of charging capacity of coin cells to which regenerated or newly produced positive electrode active materials manufactured or prepared in Comparative Examples 1 to 3 and Examples 1 to 5 are applied. [Figure 8] FIG. 1 is a graph showing the results of evaluating monocells for each of the regenerated or newly produced positive electrode active materials manufactured or prepared in Examples 1 and 2 and Comparative Examples 1 and 2, and showing the change in resistance depending on the change in SOC (State of charge;%) at 0.1 sec. [Figure 9] This is a graph showing the results of evaluating monocells for each of the regenerated or newly produced positive electrode active materials manufactured or prepared in Examples 1 and 2 and Comparative Examples 1 and 2, and showing the change in resistance as a function of the change in SOC (%) over 30 seconds. [Figure 10]1 is a graph showing the results of evaluating monocells for each of the regenerated or new positive electrode active materials produced or prepared in Examples 1 and 2 and Comparative Examples 1 and 2, where the 0.1 sec resistance is subtracted from the 30 sec resistance. [Figure 11] 2 is a flow chart of a process for regenerating a positive electrode active material according to the present invention. BEST MODE FOR CARRYING OUT THEINVENTION

[0035] The inventors have been researching a direct recycled method for recycling used positive electrodes into a positive active material with excellent battery performance without decomposing the positive active material. They found that when a used positive electrode including a current collector and a positive active material layer coated thereon is heat-treated to recover the positive active material, and a lithium precursor and a Co-containing coating agent are simultaneously added thereto and annealed, the crystal structure and the surface coating layer are both restored, improving the initial capacity and resistance characteristics of the secondary battery. They also confirmed the advantages of the process. Based on this, they continued their research and completed the present invention.

[0036] The regenerated positive electrode active material, the regenerating method thereof, and the secondary battery including the same will be described in detail below.

[0037] However, the terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor can appropriately define the concepts of terms to best describe his / her invention. Therefore, it should be understood that the embodiments described in the present specification and the configurations shown in the drawings are merely one embodiment of the present invention and do not fully represent the technical ideas of the present invention, and therefore there are various equivalents and modifications that can replace them, and they can be arranged, substituted, combined, separated or designed in various other configurations.

[0038] All technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, unless otherwise defined.

[0039] Method for regenerating positive electrode active material The method for regenerating a positive electrode active material of the present invention is characterized by comprising the steps of: (a) heat-treating a waste positive electrode having a positive electrode active material layer formed on a current collector, thereby thermally decomposing the binder and conductive material in the positive electrode active material layer, thereby separating the current collector from the positive electrode active material layer and recovering the positive electrode active material in the positive electrode active material layer; and (b) adding a lithium precursor and a Co-containing coating agent to the recovered positive electrode active material, followed by annealing. In this case, there are advantages in that the initial capacity and resistance characteristics of the secondary battery are excellent, and production costs can be reduced as a process advantage.

[0040] Hereinafter, the method for regenerating the positive electrode active material will be described in detail step by step.

[0041] (a) A step of recovering a positive electrode active material from a waste positive electrode The step (a) of recovering a positive electrode active material from a waste positive electrode according to the present invention may preferably be a step of heat-treating a waste positive electrode having a positive electrode active material layer formed on a current collector, thereby thermally decomposing the binder and conductive material in the positive electrode active material layer, thereby separating the current collector from the positive electrode active material layer, and recovering the positive electrode active material in the positive electrode active material layer. In this case, the process is simple, and the binder, conductive material, and current collector can be effectively removed cleanly.

[0042] The discarded positive electrodes may preferably be positive electrodes separated from lithium secondary batteries discarded after use, defective positive electrode sheets generated in the manufacturing process of lithium secondary batteries, or positive electrode scraps, and more preferably positive electrode scraps remaining after punching out positive electrode plates from positive electrode sheets.

[0043] The positive electrode active material layer in step (a) may preferably include a positive electrode active material, a binder, and a conductive material.

[0044] The positive electrode active material may include at least one selected from the group consisting of a nickel-cobalt-manganese (NCM)-based positive electrode active material, a nickel-cobalt-aluminum (NCA)-based positive electrode active material, and a nickel-cobalt-manganese-aluminum (NCMA)-based positive electrode active material, for example.

[0045] The positive electrode active material is preferably LiCoO 2 Lithium cobalt oxide (hereinafter referred to as "LCO"), LiMnO 2 Or LiMn 2 O 4 Lithium manganese oxide such as LiFePO 4 Lithium iron phosphate compounds such as lithium nickel cobalt aluminum oxide (NCA); LiNiO 2 and the like; nickel manganese-based lithium composite metal oxides in which nickel (Ni) in the lithium nickel oxide is partially substituted with manganese (Mn); and NCM-based lithium composite transition metal oxides in which nickel (Ni) in the lithium nickel oxide is partially substituted with manganese (Mn) and cobalt (Co). More preferably, the lithium composite metal oxide is a nickel manganese-based lithium composite metal oxide, an NCM-based lithium composite transition metal oxide, or a mixture thereof. In this case, the lithium composite metal oxide has an effect of being excellent in reversible capacity and thermal stability.

[0046] As yet another specific example, the positive electrode active material is represented by the following chemical formula 1 Li a Ni x Mn y Co z M w O 2+δ (chemical formula 1) (In the formula (1), M contains one or more selected from the group consisting of B, W, Al, Ti, and Mg, 1 < a ≤ 1.1, 0 < x < 0.95, 0 < y < 0.8, 0 < z < 1.0, 0 ≤ w ≤ 0.1, -0.02 ≤ δ ≤ 0.02, and x + y + z + w = 1. It may be a compound represented by this.)

[0047] As an example, the cathode active material can contain 60 mol% or more, preferably 80 mol% or more, more preferably 81 mol% or more, and still more preferably 81 to 95 mol% of Ni based on 100 mol% of the total of the metals excluding Li. Within this range, there is an effect of excellent initial capacity and resistance characteristics.

[0048] In this description, when the content of Ni is measured by a measurement method using IC (Ion Chromatography) or the like commonly used in the technical field to which the present invention belongs, it is not particularly limited. As a specific example, it can be measured using an IC-ICP (Inductively Coupled Plasma) analyzer, an IC-ICP-MS analyzer, or an IC-ICP-AEC analyzer, etc.

[0049] As an example, the conductive material may be a carbon-based conductive material, and preferably may be carbon black, CNT, or a mixture thereof.

[0050] As an example, the binder may be a polymer binder, and preferably may be polyvinylidene fluoride (PVdF), acrylonitrile-butadiene rubber (NBR), or a mixture thereof, and more preferably may be polyvinylidene fluoride.

[0051] In the step (a), the heat treatment may be performed, for example, at 300 to 650 °C, preferably 400 to 620 °C, more preferably 500 to 600 °C in an oxygen atmosphere. Within this range, there is an advantage that only the binder and the like are removed without melting the current collector, and the cathode active material can be easily separated from the current collector.

[0052] The heat treatment time may be preferably 10 minutes to 5 hours, more preferably 30 minutes to 5 hours, and even more preferably 30 minutes to 2 hours. Within this range, the current collector is not dissolved and only the binder and the like are removed, which has the advantage that the positive electrode active material can be easily separated from the current collector.

[0053] In this description, the heat treatment time refers to the time during which the heat treatment is performed at the heat treatment temperature, and does not include the time required to reach the heat treatment temperature.

[0054] The positive electrode active material recovered in step (a) may include, for example, single particles. In this case, the strength of the particles may be improved, and the occurrence of cracks and breakage of the particles in the positive electrode active material due to rolling may be reduced.

[0055] In this description, the term "single particle" refers to a single particle that is enlarged or has a large particle size, i.e., a single structure, in accordance with the definition generally used in the technical field to which the present invention belongs, rather than the form of an aggregated secondary particle. Here, the secondary particle refers to an aggregate formed by the aggregation of particles.

[0056] In the present description, the enlargement is not particularly limited as long as it is an enlargement method commonly used for producing single particles in the technical field to which the present invention pertains.

[0057] The single particles have an average particle size (D 50 ) may be preferably 2 to 10 μm, more preferably 2 to 8 μm, and further preferably 3 to 6 μm.

[0058] In this description, the average particle size (D 50 The average particle size (D) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured, for example, by using a laser diffraction method.50 The method for measuring the average particle size (D) is as follows: After dispersing the particles of the positive electrode active material in a dispersion medium, the particles are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT3000), and ultrasonic waves of about 28 kHz are irradiated at an output of 60 W. Then, the average particle size (D) corresponding to 50% of the cumulative volume in the measuring device is measured. 50 ) can be calculated.

[0059] The positive electrode active material may contain, for example, 10 to 100% by weight, preferably 10 to 80% by weight, and more preferably 20 to 60% by weight of single particles. Within this range, the strength of the particles is improved, and the occurrence of cracks in the positive electrode active material and the breakage of the particles due to rolling are reduced.

[0060] The oxygen used in the heat treatment may have a purity of, for example, 59% or more, preferably 70% or more, more preferably 80% or more, even more preferably 90% or more, and even more preferably 90 to 99%. Within this range, the binder and conductive material are removed without remaining, and there are advantages in that the stability of Ni in the positive electrode active material is increased and the crystal size is reduced.

[0061] The oxygen purity % may be volume % or mol %.

[0062] The purity of oxygen described herein is not particularly limited, as long as it is measured by a measurement method commonly used in the technical field to which the present invention pertains.

[0063] (b) adding a lithium precursor and a Co-containing coating agent to the recovered positive electrode active material and annealing the material; The method for regenerating a positive electrode active material of the present invention includes (b) adding a lithium precursor and a Co-containing coating agent to the recovered positive electrode active material, and annealing the material. In this case, the crystal structure and the surface coating layer are both restored, resulting in excellent initial capacity and resistance characteristics of the secondary battery, and a process advantage of reduced production costs.

[0064] The lithium precursor is preferably LiOH, Li2 CO 3 , LiNO 3 and Li 2 O, and preferably LiOH. In this case, the lithium that is insufficient in the regenerated positive electrode active material is replenished, and the crystallinity is improved, for example, by increasing the crystallinity or recovering the crystal structure, thereby improving the battery characteristics of the regenerated positive electrode active material.

[0065] The lithium precursor can be added preferably in an amount that is at least the amount of lithium that is reduced from the molar ratio of lithium in the positive electrode active material in step (a) based on the amount of lithium in the recovered positive electrode active material, and more preferably in an amount of lithium that is 0.0001 to 0.2 molar ratio relative to the molar ratio of lithium in the positive electrode active material in step (a). Within this range, the lithium that is insufficient in the regenerated positive electrode active material is replenished, and the crystallinity is improved, such as by increasing the crystallinity or recovering the crystal structure, thereby improving the battery characteristics of the regenerated positive electrode active material.

[0066] The lithium precursor may be added in an amount of preferably 1 to 40 mol %, more preferably 1 to 15 mol %, and even more preferably 1 to 10 mol %, when the total amount of lithium contained in the recovered positive electrode active material is 100 mol %. Within this range, no residual precursor that may increase resistance remains in the regenerated positive electrode active material, which is very useful for improving battery characteristics.

[0067] The Co-containing coating agent is preferably Co(OH) 2 , Co 2 O 3 , Co 3 (PO 4 ) 2 , CoF 3 , CoOOH, Co(OCOCH 3 ) 2 4H 2 O, Co(NO 3 )·6H 2 O, Co3 O 4 , Co(SO 4 ) 2 7H 2 O, and CoC 2 O 4 More preferably, the compound may be one or more selected from the group consisting of Co(OH) 2 In this case, the surface of the positive electrode active material is uniformly coated, and the battery performance such as the output characteristics and life characteristics of the battery is improved due to the increased conductivity, and corrosion and side reactions of the surface of the positive electrode active material caused by hydrogen fluoride are suppressed.

[0068] In the step (b), the Co-containing coating agent may be added to have a Co content of 1 to 25,000 ppm, preferably 1 to 15,000 ppm, more preferably 100 to 10,000 ppm, even more preferably 500 to 7,000 ppm, and even more preferably 700 to 3,000 ppm, based on the total content of the recovered positive electrode active material and the content of the additionally added lithium precursor. In this case, the surface of the positive electrode active material is uniformly coated, thereby improving the battery performance.

[0069] In this description, % and ppm are by weight unless otherwise specified.

[0070] The (b) annealing step may, for example, be performed by adding a lithium precursor and a Co-containing coating agent to the positive electrode active material and annealing the positive electrode active material in air or oxygen. 2 ) at 400 to 800 ° C, preferably 500 to 750 ° C, more preferably 550 to 750 ° C., and within this range, there is an effect of recovering the crystal structure of the positive electrode active material, improving the crystallinity such as increasing the crystallinity or recovering the crystal structure, and improving the structural stability of the positive electrode active material and the electrochemical performance of the regenerated positive electrode active material.

[0071] The annealing temperature can be adjusted within a limited range depending on the melting points of the lithium precursor and the Co-containing coating agent.

[0072] In the case of the lithium precursor, for example, LiCO 3 In the case of LiOH, the melting point is 462°C, so that annealing can be performed preferably at 400 to 600°C, more preferably at 450 to 480°C. Within this range, the crystal structure is restored, resulting in excellent battery output performance and improved structural stability and electrochemical performance of the positive electrode active material.

[0073] In the case of the Co-containing coating agent, for example, Co(OH) 2 Since the melting point of the positive electrode active material is 168°C, it can be annealed preferably at 400 to 800°C, more preferably at 500 to 750°C, and further preferably at 550 to 750°C. Within this range, the crystal structure is restored, resulting in excellent output performance of the battery and improved structural stability and electrochemical performance of the positive electrode active material.

[0074] The annealing temperature may be preferably a temperature exceeding the melting points of the lithium precursor and the Co-containing coating agent, but if it exceeds 1000°C, thermal decomposition of the positive electrode active material may occur, resulting in a decrease in battery performance, and therefore, the annealing temperature is preferably 1000°C or less.

[0075] In the (b) annealing step, the method of adding the lithium precursor and the Co-containing coating agent to the recovered positive electrode active material may be a method of adding the lithium precursor and the Co-containing coating agent in a solid phase or liquid phase to the recovered positive electrode active material. As another example, a method of adding a lithium precursor solution and a Co-containing coating agent solution to the recovered positive electrode active material and spray drying may be used, in which case there are advantages that particle aggregation due to normal drying is reduced, the process of mixing the solid-phase lithium precursor can be omitted, and the material can be obtained in the form of powder rather than lumps.

[0076] The lithium precursor solution and the Co-containing coating agent solution may be, for example, a lithium compound that is soluble in an aqueous solution or an organic solvent.

[0077] FIG. 11 below is a flow chart of a process for regenerating a positive active material according to one embodiment of the present invention.

[0078] Referring to Fig. 11, first, cathode scraps are prepared as waste cathodes (step S10). For example, a slurry is prepared by mixing NCM-based lithium transition metal composite oxide containing 60 mol% or more of Ni based on a total of 100 mol% of the remaining metals excluding Li, carbon black, and polyvinylidene fluoride, and adding NMP (N-methyl pyrrolidone). The slurry is coated on aluminum foil and dried in a vacuum oven at about 120°C to prepare a cathode sheet. A cathode plate of a certain size is punched out from this, and the remaining cathode scraps can be prepared.

[0079] The positive electrode scrap has a positive electrode active material layer on an aluminum foil, and the positive electrode active material layer has a structure in which the positive electrode active material and the conductive material are bound by the binder after the solvent is evaporated, and therefore, when the binder is removed, the positive electrode active material is separated from the aluminum foil.

[0080] Next, the prepared cathode scrap is crushed into an appropriate size (step S20). Here, crushing includes cutting or shredding the cathode scrap into a size that is easy to handle. As a specific example, the crushed cathode scrap may have a size of 1 cm x 1 cm. The crushing may be performed using various dry grinding equipment such as a hand mill, a pin mill, a disc mill, a cutting mill, or a hammer mill, or may be performed using a high-speed cutter to increase productivity.

[0081] The crushing may be performed or the size of the pieces may be determined in consideration of the handling of the cathode scrap and the properties required for equipment used in subsequent processes. For example, when equipment capable of continuous processing is used, the cathode scrap should have good fluidity and therefore should be crushed into smaller pieces.

[0082] Next, the positive electrode scrap is heat-treated to recover the positive electrode active material (step S30). Here, the heat treatment is performed to thermally decompose the binder in the positive electrode active material layer.

[0083] The heat treatment is preferably carried out under oxygen with a purity of 80% or more, and more preferably under oxygen with a purity of 90% or more. In this case, the stability of Ni can be ensured in the waste cathode using high-nickel (High-Ni) cathode material, and the binder and conductive material can be cleanly removed. When the heat treatment is carried out in a reducing gas or inert gas atmosphere, the binder and conductive material are carbonized without being thermally decomposed. When carbonized, the carbon components remain on the surface of the cathode active material, which reduces the performance of the recycled cathode active material. However, when the heat treatment is carried out by introducing oxygen, the carbon components in the binder and conductive material react with the oxygen to produce CO, CO 2 The binder and conductive material are both removed because the gas disappears as a gas such as benzene.

[0084] The heat treatment is preferably carried out at 300 to 650°C, specifically at 590°C. If the temperature is less than 300°C, it is difficult to remove the binder, making it impossible to separate the current collector. If the temperature exceeds 650°C, the current collector melts, causing a problem that it is impossible to separate the current collector.

[0085] The heat treatment is preferably performed at a temperature increase rate of 1 to 20° C. / min, more preferably 3 to 10° C. / min, and specifically 5° C. / min. Within this range, the heat treatment can be performed without putting strain on the heat treatment equipment, and there are advantages in that no thermal shock is caused to the cathode scrap.

[0086] The heat treatment can be carried out for a period of time that allows the binder to be sufficiently pyrolyzed, for example, preferably for 30 minutes or more, more preferably for 30 minutes to 5 hours, and specifically for about 30 minutes. Within this range, the binder is sufficiently pyrolyzed, and there is an effect of excellent pyrolysis efficiency.

[0087] The heat treatment may be carried out using various types of furnaces, for example, a box-type furnace, or, in consideration of productivity, a rotary kiln capable of continuous treatment.

[0088] After the heat treatment, the material can be cooled slowly or rapidly in air.

[0089] Next, a lithium precursor and a Co-containing coating agent are added to the recovered positive electrode active material, and the resulting mixture is annealed (step S40).

[0090] It is important that the annealing step is performed by adding a lithium precursor and a Co-containing coating agent to the recovered positive electrode active material, in which case, loss of lithium and loss of the coating layer in the positive electrode active material may occur during the previous step S30, and such loss of lithium and coating layer is replenished in step S40. Moreover, in step S40, the crystal structure of the positive electrode active material is restored through annealing, thereby restoring or further improving the characteristics of the regenerated positive electrode active material to the level of a new positive electrode active material that has never been used.

[0091] During the previous step S30, a deformed structure may occur on the surface of the positive electrode active material. As a specific example, in the case of a positive electrode active material that is an NCM-based lithium composite transition metal oxide, Ni is converted into [NiCO 3 2Ni(OH) 2 )H 2O], a spinel structure may be formed. If a battery is manufactured in this state, the battery characteristics, such as a decrease in capacity, may be deteriorated. In the present invention, the crystal structure is restored and the surface is uniformly coated through step S40. As a specific example, the positive electrode active material, which is an NCM-based lithium composite transition metal oxide, is restored to a hexagonal crystal structure again and the surface is uniformly coated with a Co-containing coating agent. As a result, the initial characteristics can be restored or improved to a level similar to that of a new positive electrode active material, and the structural stability and electrochemical performance of the positive electrode active material are improved. Here, "new" or "fresh" is the opposite concept of "regenerated" and means that it is made for the first time, and is the same word as "raw material" used in the examples.

[0092] The lithium precursor in step S40 is LiOH, Li 2 CO 3 , LiNO 3 , and Li 2 O, and LiOH is used as a specific example.

[0093] The lithium precursor is preferably added in an amount at least equal to the molar ratio of the lost lithium, compared to the molar ratio of lithium and other metals in the new positive electrode active material used in the positive electrode active material layer. Addition of an amount of lithium precursor that is excessively greater than the amount of lost lithium leaves unreacted lithium precursor in the regenerated positive electrode active material, which increases resistance, so it is necessary to add an appropriate amount of lithium precursor.

[0094] For example, when the amount of lithium contained in the positive electrode active material recovered after the heat treatment in S30 is taken as 100 mol % in total, the lithium precursor can be added in an amount corresponding to 1 to 40 mol %, preferably 1 to 15 mol %, and more preferably 1 to 10 mol %.

[0095] As yet another example, when the molar ratio of lithium to other metals in the newly produced positive electrode active material is 1, the lithium precursor can be added in an amount such that the lithium has a molar ratio of 0.001 to 0.4, and preferably, the lithium precursor can be added in an amount such that the lithium has a molar ratio of 0.01 to 0.2.

[0096] As a specific example, when the lithium precursor is added in a molar ratio (based on lithium metal) of 0.09 to 0.1, which is the ratio of the lithium content lost in the new positive electrode active material based on the results of ICP analysis, the capacity improvement effect is shown to the same level as that of the new positive electrode active material. Here, the results of ICP analysis have an error value of about ±0.02.

[0097] The Co-containing coating agent in step S40 is Co(OH). 2 , Co 2 O 3 , Co 3 (PO 4 ) 2 , CoF 3 , CoOOH, Co(OCOCH 3 ) 2 4H 2 O, Co(NO 3 )·6H 2 O, Co 3 O 4 , Co(SO 4 ) 2 7H 2 O, and CoC 2 O 4 The compound may be one or more selected from the group consisting of Co(OH) 2 Use.

[0098] For example, the Co coating agent may be added so that the Co content is 1 to 25,000 ppm, preferably 1 to 15,000 ppm, more preferably 100 to 10,000 ppm, further preferably 500 to 7,000 ppm, and even more preferably 700 to 3,000 ppm, based on the total content of the recovered positive electrode active material and the content of the additionally added lithium precursor.

[0099] As a specific example of a method for adding the lithium precursor and the Co-containing coating agent to the recovered positive electrode active material, the lithium precursor and the Co-containing coating agent in powder form can be mixed so that the powders are well mixed with each other, and then mixed with the recovered positive electrode active material so that they are uniformly mixed, and then annealed.

[0100] The annealing is carried out in oxygen under conditions of, for example, 400 to 800°C, preferably 500 to 750°C, more preferably 550 to 750°C, and this temperature must be modified within a limited range depending on the type of lithium precursor and Co-containing coating agent.

[0101] The annealing temperature is preferably a temperature exceeding the melting points of the lithium precursor and the Co-containing coating agent. However, at temperatures exceeding 1000°C, thermal decomposition of the positive electrode active material occurs, resulting in a decrease in performance, so the annealing temperature should not exceed 1000°C. 2 CO 3 Co(OH) is used as a Co-containing coating agent. 2 When using LiOH as the lithium precursor, Co(OH) is preferably used as the Co-containing coating agent. 2 When using the above, the annealing temperature is suitably 400 to 800°C, more preferably 500 to 750°C, and further preferably 550 to 750°C.

[0102] The annealing time is, for example, 1 hour or more, preferably 15 hours or less, and more preferably 4 to 6 hours. If the annealing time is long, the crystal structure recovery and surface coating can be sufficiently performed, but even if the annealing is performed for a long time, the performance is not significantly affected. In this case, the annealing equipment can be the same as or similar to that of the heat treatment step S30.

[0103] If the molar ratio of lithium:other metals in the positive electrode active material is set to 1:1 in the annealing step S40, the lithium in the positive electrode active material reacts with the Co-containing coating agent, and the molar ratio of lithium:other metals in the positive electrode active material becomes less than 1:1, and such a regenerated positive electrode active material cannot fully demonstrate 100% of the battery capacity. However, if the lithium precursor is excessively added in the annealing step S40 so that it is contained in an amount of 0.0001 to 0.1 molar ratio more than the other metals in the positive electrode active material, a surface protective layer is formed by the Co-containing coating agent, and the molar ratio of lithium:other metals in the positive electrode active material naturally becomes 1:1, and the capacity reduction of the battery does not occur.

[0104] In this way, the method for regenerating a positive electrode active material according to this embodiment has the advantage that the process is continuous and the crystallization recovery process and the surface coating process are carried out simultaneously in one step.

[0105] positive electrode active material The positive electrode active material of the present invention is at least one selected from the group consisting of nickel-cobalt-manganese (NCM)-based positive electrode active materials, nickel-cobalt-aluminum (NCA)-based positive electrode active materials, and nickel-cobalt-manganese-aluminum (NCMA)-based positive electrode active materials, and is characterized in that it contains at least 60 mol % of Ni based on 100 mol % of the total of the remaining metals excluding Li, and contains a Co-containing coating agent. In this case, there is an effect that the battery performance such as the output characteristics and life characteristics of the battery is improved due to the increased conductivity, and corrosion and side reactions of the surface of the positive electrode active material caused by hydrogen fluoride are suppressed.

[0106] The positive electrode active material is preferably LiCoO 2 Lithium cobalt oxide (hereinafter referred to as "LCO"), LiMnO 2 Or LiMn 2 O 4 Lithium manganese oxide such as LiFePO 4Lithium iron phosphate compounds such as; lithium nickel cobalt aluminum oxide (NCA); LiNiO 2 Lithium nickel oxide such as; nickel manganese-based lithium composite metal oxide in which part of nickel (Ni) in the lithium nickel oxide is replaced with manganese (Mn); and NCM-based lithium composite transition metal oxide in which part of nickel (Ni) in the lithium nickel oxide is replaced with manganese (Mn) and cobalt (Co). One or more selected from the group consisting of can be included, and in this case, there is an effect of being excellent in electrochemical performance, resistance characteristics, capacity characteristics, etc.

[0107] As a specific example, the positive electrode active material has the following chemical formula 1 Li a Ni x Mn y Co z M w O 2+δ (Chemical formula 1) (In the chemical formula 1, M includes one or more selected from the group consisting of B, W, Al, Ti, and Mg, 1 < a ≤ 1.1, 0 < x < 0.95, 0 < y < 0.8, 0 < z < 1.0, 0 ≤ w ≤ 0.1, -0.02 ≤ δ ≤ 0.02, and x + y + z + w = 1). A compound represented by can be included, and in this case, there is an effect of being excellent in electrochemical performance, resistance characteristics, capacity characteristics, etc.

[0108] Preferably, based on 100 mol% of the total of the metals excluding Li, the positive electrode active material contains 80 mol% or more of Ni, more preferably 81 mol% or more, and still more preferably 81 - 95 mol%. Within this range, there is an effect of being excellent in initial capacity and resistance characteristics.

[0109] The Co-containing coating agent is preferably Co(OH) 2 、Co 2 O 3 、Co 3 (PO 4 ) 2 、CoF3 , CoOOH, Co(OCOCH 3 ) 2 4H 2 O, Co(NO 3 )·6H 2 O, Co 3 O 4 , Co(SO 4 ) 2 7H 2 O, and CoC 2 O 4 More preferably, the compound may be one or more selected from the group consisting of Co(OH) 2 In this case, the surface of the positive electrode active material is uniformly coated, and the battery performance such as the output characteristics and life characteristics of the battery is improved due to the increased conductivity, and corrosion and side reactions of the surface of the positive electrode active material due to hydrogen fluoride are suppressed.

[0110] For example, the positive active material may include single particles. In this case, the strength of the particles may be improved, and the occurrence of cracks and breakage of the particles in the positive active material due to rolling may be reduced.

[0111] In this description, the term "single particle" refers to a single particle that is enlarged or has a large particle size, i.e., a single structure, in accordance with the definition generally used in the technical field to which the present invention belongs, rather than the form of an aggregated secondary particle. Here, the secondary particle refers to an aggregate formed by the aggregation of particles.

[0112] The single particles have an average particle size (D 50 ) may be preferably 2 to 10 μm, more preferably 2 to 8 μm, and further preferably 3 to 6 μm. Within this range, the strength of the particles is improved, and there is an effect of reducing the occurrence of cracks in the positive electrode active material due to rolling and the breakage of the particles.

[0113] The positive electrode active material may contain, for example, 10 to 100% by weight, preferably 10 to 80% by weight, and more preferably 20 to 60% by weight of single particles. Within this range, the strength of the particles is improved, and the occurrence of cracks in the positive electrode active material and breakage of the particles due to rolling can be reduced.

[0114] The positive electrode active material may preferably be a regenerated positive electrode active material, which has the advantages of being economical and productive.

[0115] secondary battery The secondary battery of the present invention includes the positive electrode active material. In this case, the secondary battery has excellent initial capacity and resistance characteristics, and is advantageous in terms of process. In addition, since no acid or organic solvent is used in the recovery and regeneration process of the positive electrode active material, the secondary battery is environmentally friendly. In particular, since the initial water washing process is omitted, the secondary battery has excellent economic efficiency and productivity.

[0116] The secondary battery of the present invention may include all of the above-mentioned positive electrode active material and the regeneration method thereof, and therefore, a duplicate description thereof will be omitted here.

[0117] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical spirit of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.

[0118] [Example] Example 1 The cathode scraps discarded after punching out the cathode plates (current collector: aluminum foil, cathode active material: single particles of NCMA with nickel content of 80 mol%) were crushed and oxidized at 590℃ for 30 minutes in oxygen with a purity of 90% or more to remove the binder and conductive material, and the cathode active material was separated and then recovered. The temperature was increased at a rate of 5℃ / min until the heat treatment temperature was reached.

[0119] It was confirmed that the molar ratio of lithium to other metals in the recovered positive electrode active material was reduced by 0.02 molar ratio level compared to the molar ratio of lithium to other metals in the raw positive electrode active material.

[0120] In order to replenish the lost lithium, a lithium precursor LiOH was added in an amount that would result in 5 mol% lithium when the total lithium content of the recovered positive active material was taken as 100 mol%, and a Co-containing coating agent Co(OH) was added in an amount that would result in a Co content of 1,000 ppm based on the total content of the recovered positive active material and the additional lithium precursor LiOH. 2 The mixture was then annealed in oxygen at 700°C for 5 hours.

[0121] A regenerated positive electrode active material was obtained from the annealed positive electrode active material.

[0122] In this description, the molar ratio of lithium and other metals in the positive electrode active material was measured using an ICP analyzer. In this case, the measurement can be performed using a general ICP analyzer commonly used in laboratories, and there is no deviation due to the measurement device or method.

[0123] Example 2 In the annealing step of Example 1, the Co-containing coating agent was added to the positive electrode active material so that the Co content was 2,000 ppm based on the total content of the recovered positive electrode active material and the lithium precursor LiOH to be added. 2 A regenerated positive electrode active material was produced in the same manner as in Example 1, except that the above was added.

[0124] Example 3 In the annealing step of Example 1, the Co-containing coating agent was added to the positive electrode active material so that the Co content was 5,000 ppm based on the total content of the recovered positive electrode active material and the lithium precursor LiOH to be added.2 A regenerated positive electrode active material was produced in the same manner as in Example 1, except that the above was added.

[0125] Example 4 In the annealing step of Example 1, the Co-containing coating agent was added to the positive electrode active material so that the Co content was 10,000 ppm based on the total content of the recovered positive electrode active material and the lithium precursor LiOH to be added. 2 A regenerated positive electrode active material was produced in the same manner as in Example 1, except that the above was added.

[0126] Example 5 In the annealing step of Example 1, the Co-containing coating agent was added to the positive electrode active material so that the Co content was 20,000 ppm based on the total content of the recovered positive electrode active material and the lithium precursor LiOH to be added. 2 A regenerated positive electrode active material was produced in the same manner as in Example 1, except that the above was added.

[0127] Comparative Example 1 Fresh single particles of NCMA were used as the positive electrode active material.

[0128] Comparative Example 2 A regenerated positive electrode active material was prepared in the same manner as in Example 1, except that in the annealing step, only the lithium precursor was added and annealed.

[0129] Comparative Example 3 In the annealing step of Example 1, only the lithium precursor was added to the positive active material, and after annealing, the Co-containing coating agent was added to the positive active material so that the Co content was 1,000 ppm based on the total content of the recovered positive active material and the additional lithium precursor LiOH. 2The regenerated positive electrode active material was produced by adding and heat-treating at 700°C for 5 hours to perform surface coating.

[0130] [Test Example I: SEM Analysis] The regenerated or new positive electrode active materials manufactured or prepared in Examples 1 to 5 and Comparative Examples 1 and 2 were photographed by an SEM device, and the photographs are shown in Figs. 1 to 6. The SEM photographs were taken by a general SEM device commonly used in laboratories. Specifically, the SEM photographs were taken by using a Hitachi S-4200. However, there is no deviation due to the measurement device or method.

[0131] As can be seen from Figure 1 below, it was confirmed that a protective layer was formed on the surface of the fresh positive electrode active material of Comparative Example 1. In Figure 1, the arrow indicates the surface protective layer.

[0132] FIG. 2 shows the positive electrode active material recovered from the positive electrode scrap after heat treatment. It was confirmed that the binder and conductive material had been removed and the surface protective layer had been lost from the positive electrode active material.

[0133] FIG. 3 shows the positive electrode active material after simultaneously adding a lithium precursor and a Co-containing coating agent to the positive electrode active material recovered in Examples 1 to 4 and annealing the material. It was confirmed that the crystal structure and the surface protective layer were restored.

[0134] FIG. 4 shows Comparative Example 2, in which only a lithium precursor was added to the recovered positive electrode active material and annealed. It was confirmed that the crystal structure was restored, but the surface protective layer was reduced.

[0135] Fig. 5 is an SEM photograph of the positive electrode active material regenerated in Example 4, and it was confirmed that the crystal structure was restored and a surface protective layer was formed. In Fig. 5, the arrow indicates the surface protective layer formed on the surface of the positive electrode active material, and it was confirmed that some aggregation occurred in the surface protective layer. The left side of Fig. 5 is magnified at 10.0K, and the right side is magnified at 20.0K.

[0136] Figure 6 is an SEM photograph of the positive electrode active material regenerated in Example 5. It was confirmed that a protective layer was formed on the surface of the positive electrode active material, but the surface of the positive electrode active material was agglomerated with the Co-containing coating agent, resulting in a slight decrease in uniformity. In Figure 6, the arrow indicates the surface protective layer formed on the surface of the positive electrode active material. The left side of Figure 6 is magnified at 10.0K, and the right side is magnified at 20.0K.

[0137] [Test Example II: Evaluation of CHC Cell] The electrochemical performance of the regenerated or new positive active materials obtained in Examples 1 to 5 and Comparative Examples 1 to 3 was measured through the CHC cell evaluation as follows, and the results are shown in FIG. 7 and Table 1 below. *Evaluation of CHC cell: 97.5% by weight of recycled positive electrode active material, 1% by weight of carbon black as conductive material, and 1.5% by weight of PVdF as binder were weighed and mixed with NMP to produce a slurry. This was coated on aluminum foil to produce a positive electrode, and then a coin half cell (CHC) was produced. The voltage was set to 3-4.3V, charging and discharging was performed at 0.1C / 0.1C, and the electrochemical performance (charge capacity, discharge capacity, and efficiency) was evaluated under conditions that included ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 3:7 (weight ratio) as electrolyte and other additives.

[0138] As shown in Figure 7 below, the initial capacity performance of the regenerated positive electrode active materials prepared in Examples 1 to 4 was improved compared to Comparative Example 2, confirming the benefits of the process. In addition, although the initial capacity performance of the regenerated positive electrode active material prepared in Example 5 was somewhat low, the process benefits of saving time, energy, and equipment were confirmed by simultaneously adding the lithium precursor and the Co-containing coating agent in the annealing step.

[0139] [Table 1]

[0140] As shown in Table 1, it was confirmed that the initial capacity performance of the regenerated positive electrode active materials prepared in Examples 1 to 4 was improved. In particular, in the case of Example 1, the improvement in the initial capacity performance was significantly improved compared to Comparative Examples 2 and 3. In addition, it was confirmed that the initial capacity performance of the regenerated positive electrode active material prepared in Example 5 was somewhat low, but that the lithium precursor and the Co-containing coating agent were simultaneously added in the annealing step, thereby providing process benefits that can save time, energy, and equipment.

[0141] [Test Example III: Evaluation of Monocell] The HPPC resistance characteristics and capacity retention of the regenerated or new positive electrode active materials manufactured or prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were measured through the evaluation of mono cells as described below, and the results are shown in Figures 8 to 10 and Table 2. The mono cells manufactured in Examples 1 and 2 and Comparative Examples 1 and 2 were measured three times and the results are shown in the graphs in Figures 8 to 10.

[0142] * Manufacturing of monocell: The same positive electrode active material slurry as that used for the coin cell was applied to an aluminum foil having a thickness of 20 μm, dried at 130°C for 1 hour, and then punched out to a size of 30 mm x 42 mm to manufacture a positive electrode.

[0143] Meanwhile, a negative electrode active material slurry was prepared by mixing 95.6 wt% of a 5:5 mixture of natural graphite and artificial graphite with 3.3 wt% of conductive material and 1.1 wt% of binder. The slurry was applied to a copper foil having a thickness of 10 μm, rolled and dried, and then punched into a size of 31 mm×43 mm to prepare a negative electrode.

[0144] The prepared positive and negative electrodes were joined with a separator, and an electrolyte solution having a weight ratio of ethylene carbonate (EC):ethyl methyl carbonate (EMC)=3:7 was injected to prepare a polymer cell type mono cell for testing.

[0145] *Measurement of resistance change according to SOC: The resistance change according to SOC was measured for the manufactured mono cells. Resistance according to SOC was measured using the HPPC (Hybrid Pulse Power Characterization) method, and both discharge resistance and charge resistance were measured by applying a current of 2C for 10 seconds. SOC was measured at six points: 95%, 80%, 50%, 20%, 10% and 5%.

[0146] A pulse discharge (DC-IR measurement) was performed for each SOC section, and the resistance was recorded. The resistance was calculated by dividing the change in voltage during discharge by the discharge current according to the following Equation 1.

[0147] [Formula 1] R=V / I (Here, R is the resistance, V is the change in voltage that occurs during discharge, and I is the discharge current.)

[0148] The diffusion resistance is calculated by subtracting the 0.1 sec resistance from the 30 sec resistance, using the following formulas 2 to 4.

[0149] [Formula 2] 0.1sec resistance=R(ohm)+R(ct)

[0150] [Formula 3] 30sec resistance=R(ohm)+R(ct)+R(diff)

[0151] [Formula 4] R(diff)=30sec resistance-0.1sec resistance (In the above formulas 2 to 4, R(ohm) is an ohmic resistance, which indicates the resistance in the cell, R(ct) is a charge transfer resistance, which indicates the resistance when lithium moves from the electrolyte to the positive electrode active material, and R(diff) is a diffusion resistance, which indicates the resistance when lithium that has penetrated into the positive electrode active material is settled deep inside the positive electrode active material.)

[0152] *Measurement of capacity retention and resistance increase: The produced mono-cell was subjected to 100 charge / discharge cycles at a constant current of 0.3 C in the range of 2.5 to 4.25 V at 45° C., and the capacity and resistance of the mono-cell battery were measured, and the results are shown in Table 2 below. Here, the capacity retention (Capacity Retention, %) is the ratio of the capacity at the 100th cycle to the capacity at the 1st cycle, the capacity retention vs. Comparative Example 1 (Capacity Retention vs. Comparative Example 1, %) is the ratio of the capacity at the 100th cycle of Comparative Example 2 and Examples 1 and 2 to the capacity at the 100th cycle of Comparative Example 1, and the resistance increase (Resistance Increase, %) is the ratio of the resistance at the 100th cycle to the resistance at the 1st cycle.

[0153] As shown in Figures 8 to 10 below, in Examples 1 and 2, the R(ct) and R(ohm) resistances are higher in some areas than in Comparative Example 2, in which only the lithium precursor was added without adding a Co-containing coating agent during annealing, but the effect of improving the diffusion resistance was confirmed. If the diffusion resistance is reduced, the resistance required for Li that has penetrated into the positive electrode active material to settle deep inside the positive electrode active material is reduced, resulting in improved battery performance.

[0154] [Table 2]

[0155] As shown in Table 2, in Examples 1 and 2 in which a lithium precursor and a Co-containing coating agent were simultaneously added to the recovered positive electrode active material and annealed, the capacity retention rate and the resistance increase rate after 100 cycles were similar or equivalent to those of Comparative Example 1 and were superior to those of Comparative Example 2, and therefore it was confirmed that the battery performance was improved.

Claims

1. (a) subjecting a waste positive electrode having a positive electrode active material layer formed on a current collector to a heat treatment to thermally decompose a binder and a conductive material in the positive electrode active material layer, thereby separating the current collector from the positive electrode active material layer and recovering the positive electrode active material in the positive electrode active material layer; (b) adding a lithium precursor and a Co-containing coating agent to the recovered positive electrode active material, and annealing the resulting mixture.

2. 2. The method of claim 1, wherein the positive electrode active material layer includes at least one selected from the group consisting of nickel-cobalt-manganese (NCM)-based positive electrode active materials, nickel-cobalt-aluminum (NCA)-based positive electrode active materials, and nickel-cobalt-manganese-aluminum (NCMA)-based positive electrode active materials, and includes at least 60 mol % of Ni based on a total of 100 mol % of the remaining metals excluding Li.

3. 2. The method for regenerating a positive electrode active material according to claim 1, wherein in step (a), the heat treatment is performed at 300 to 650° C. in an oxygen atmosphere.

4. The oxygen has a purity of 59% or more (O 2 4. The method for regenerating a positive electrode active material according to claim 3, wherein the positive electrode active material is a

5. The method for regenerating a positive electrode active material according to claim 1 , wherein the positive electrode active material recovered in step (a) includes single particles.

6. 2. The method of claim 1, wherein in step (b), the lithium precursor is added in an amount corresponding to 1 mol% to 40 mol% when the total amount of lithium contained in the recovered positive electrode active material is 100 mol%.

7. 2. The method of claim 1, wherein in step (b), the Co-containing coating agent is added to have a Co content of 1 to 25,000 ppm based on a total content of the recovered positive active material and an additional lithium precursor.

8. The lithium precursor is LiOH, Li 2 CO 3 , LiNO 3 , and Li 2 The method for regenerating a positive electrode active material according to claim 1 , wherein the positive electrode active material contains one or more of O.

9. The Co-containing coating agent is Co(OH) 2 , Co 2 O 3 , Co 3 (P.O. 4 ) 2 , CoF 3 , CoOOH, Co(OCOCH 3 ) 2 ・4H 2 O, Co(NO 3 ) 6H 2 O.C.O. 3 O 4 , Co(SO 4 ) 2 ・7H 2 O, and CoC 2 O 4 The method for regenerating a positive electrode active material according to claim 1 , wherein the active material is one or more selected from the group consisting of:

10. 2. The method of claim 1, wherein the annealing is performed at 400 to 800° C.

11. At least one selected from the group consisting of nickel-cobalt-manganese (NCM)-based positive electrode active materials, nickel-cobalt-aluminum (NCA)-based positive electrode active materials, and nickel-cobalt-manganese-aluminum (NCMA)-based positive electrode active materials, containing 60 mol % or more of Ni based on 100 mol % of the total of the remaining metals excluding Li; A positive electrode active material, the surface of which is coated with a Co-containing coating agent.

12. The Co-containing coating agent is Co(OH) 2 , Co 2 O 3 , Co 3 (P.O. 4 ) 2 , CoF 3 , CoOOH, Co(OCOCH 3 ) 2 ・4H 2 O, Co(NO 3 ) 6H 2 O.C.O. 3 O 4 , Co(SO 4 ) 2 ・7H 2 O, and CoC 2 O 4 The positive electrode active material according to claim 11, which is one or more selected from the group consisting of:

13. The positive electrode active material according to claim 11 , comprising a single particle.

14. The positive electrode active material according to claim 11, wherein the positive electrode active material is a regenerated positive electrode active material.

15. A secondary battery comprising the positive electrode active material according to any one of claims 11 to 14.

Citation Information

Patent Citations

  • Positive electrode substance for lithium ion battery, and method for manufacturing the same

    JP2016051503A

  • Positive electrode active material for a lithium secondary battery containing a lithium metal oxide having a multilayer structure and a positive electrode containing the same

    JP2018523895A

  • Positive electrode active material for secondary battery, method for producing the same, and secondary battery including the same

    JP2020504415A

  • Positive electrode active material for secondary battery, method for producing the same, and lithium secondary battery including the same

    JP2021508161A

  • Positive electrode active material, method for producing positive electrode active material, positive electrode containing positive electrode active material, and lithium secondary battery

    JP2022514966A